KalyeYaan a cycling route network plan of Quezon City’s Cultural Properties as the landscape narrative of Philippine independence - Albarillo, Martin B. (College of Architecture, University of the Philippines Diliman, 2025)
Despite recent developments in cycling infrastructure in Metro Manila, a significant gap remains in the design of spaces that both support cyclists and foster recognition of the cultural landscape. At the same time, Quezon City's cultural properties face threats from rapid urban growth, lack of dedicated space for cultural engagement, and diminished public appreciation. This thesis addresses the challenges by proposing cycling route network plan that integrates cultural spaces tied to the Philippine Revolutions. The study aims to enhance community appreciation of Quezon City’s cultural heritage while promoting cycling as a sustainable mode of transport. Through a mixed-methods approach involving remote sensing, desk research, site visits, surveys, and key informant interviews, a model site was developed that synthesizes both cycling infrastructure and cultural property interventions. The analysis evaluated existing weaknesses in Quezon City’s Freedom Trail project and provided recommendations for improved connectivity, safety, and cultural visibility. The research culminates in five design principles focused on enhancing cyclability and cultural appreciation, with scenarios in relation to the Katipunan and EDSA Revolution. These routes vary in distance and experience, offering tailored cultural journeys. The outcome is an experiential landscape planning framework that merges heritage preservation, active mobility, and recreational tourism. The study provides a replicable model for other historically rich cities in the Philippines and highlights the role of landscape planning in reconnecting communities with national identity and history.